Real-world use of PCSK-9 inhibitors by early adopters: cardiovascular risk factors, statin co-treatment, and short-term adherence in routine clinical practice - Fairman KA; Davis LE; Sclar DA (Dove Medical Press, 2017)
Kathleen A Fairman, Lindsay E Davis, David A Sclar Department of Pharmacy Practice, College of Pharmacy, Midwestern University-Glendale, Glendale, AZ, USA Background: Inconsistency of real-world medication use with labeled indications may affect cost and clinical value of pharmacotherapy. PCSK-9 inhibitors are labeled in the US for use with statins to reduce low-density lipoprotein cholesterol in patients with atherosclerotic cardiovascular disease (ASCVD) or familial hypercholesterolemia (FH). Objective: To assess consistency with labeled indications and treatment persistency for early (first 5 post-launch months) adopters of PCSK-9 inhibitor pharmacotherapy. Methods: Retrospective analysis of commercially insured cohorts derived from the Truven Health MarketScan® database was performed. Subjects were aged 18–64 years, initiated PCSK-9 inhibitor or highest-intensity statin (rosuvastatin 40 mg/day or atorvastatin 80 mg/day) pharmacotherapy from August to December 2015, and were enrolled throughout 2015 and during separate baseline (pre-treatment) periods of 6 and 18 months. Baseline ASCVD, FH, and ASCVD events (myocardial infarction, transient ischemic attack, and cerebrovascular occlusion) were measured. Persistency was measured through December 2015 for subcohorts of patients initiating treatment from August to September 2015. Results: Baseline disease rates were higher for patients treated with PCSK-9 inhibitors (n=390) compared with highest-intensity statins (n=26,306): ASCVD (68.5% vs 33.4%, respectively); FH (39.7% vs 15.5%); both P<0.001. In 18 months pre-treatment, 35.6% of PCSK-9 inhibitor-treated patients had ≥1 ASCVD event, and 87.9% had a labeled indication. Rates of 60-day nonpersistency for PCSK-9 inhibitors and highest-intensity statins were 33.3% and 39.8%, respectively (P=0.207). During PCSK-9 inhibitor pharmacotherapy, 33.8% of patients had evidence of statin supply and, of those initiating treatment from August to September, 40.9% filled ≤1 statin prescription. Of those with sustained pre-treatment statin use, 34.8% had no statin supply during PCSK-9 inhibitor pharmacotherapy. Conclusion: Among early-adopting PCSK-9 inhibitor-treated patients, the off-label diagnosis rate was 12%; a majority lacked statin co-treatment; and one third filled prescriptions for ≤60 days. Inconsistency with labeled uses may reflect prescriber/patient decisions, health-insurance coverage determinations, or statin intolerance not reported on claims. Keywords: hyperlipidemia, PCSK-9 inhibitors, alirocumab, evolocumab, off-label use, specialty medications